Vibrations of Plate Strips with Internal Periodic Structure - MARCZAK, Jakub; JĘDRYSIAK, Jarosław (Engineering Transactions, 2015)
In this note vibrations of thin periodic plate strips with periodically distributed systems of three concentrated masses are analysed. Results of the non-asymptotic tolerance model are compared to those by the exact discrete model. In an example, these models are used to calculate lower and higher frequencies of the travelling wave related to the internal periodic structure.